Bangkit dari Kekelaman: Gambaran Psychological Well Being Korban Terorisme Poso - Vanda Leony Agnesila Pombadju; Sri Aryanti Kristianingsih; Tony Tampake (Wacana Psikokultural, 2024)
This study is based on the tragic event of a group of terrorists that occurred on May 11, 2021 in Kalimago Village, Poso Regency, Central Sulawesi. The terror killed four civilians who were working in their gardens. Losing family members due to tragic events can cause various emotional reactions, which makes their lives difficult. In this study, the context of the victims referred to is families whose members died as a result of acts of terrorism, and are called secondary victims. The victims' daily lives are disrupted by feelings of grief, helplessness, despair, revenge, and very severe trauma. It is very important for victims to have a good mental state at this time. Therefore, psychological well-being is very important for victims to have. Using a qualitative research method, case study approach to P1 and P2, this study aims to explore the description of the psychological well-being of Poso terrorism victims. The results of the study showed that the victims did not have good psychological well-being because the trauma had not recovered and prevented the victims from functioning fully. In addition, the researcher found that the social context that was expected to help victims recover from trauma was not optimal.